Utilization of Barracuda Fish Skin Gelatin (Sphyraena) in Making Body Lotion with the Addition of Liquid Smoke as an Antioxidant and Antibacterial - Fronthea Swastawati; Syarifah Sufi Al Hayat; Eko Susanto (Universitas Gadjah Mada, 2023)
Gelatin can be used as an emulsifier, thickener, and humectant in body lotions. Body lotion must contain natural ingredients that can prevent skin damage such as liquid smoke, which is a natural ingredient that can be used as an antioxidant and antibacterial. The purpose of this study was to determine the potential of gelatin on the features of body lotion and the effect of adding liquid immediately as an antioxidant and antibacterial. The treatments used were gelatin with different concentrations (0%, 1%, 3%, and 5%) in the opening study and liquid smoke concentrations of 0%, 0.3%, 0.5%, and 0.7% in the main study with three repetition times. Parameters observed were viscosity, hedonic, pH, antioxidant activity, and TPC. The analysis revealed that all test parameters had a significant effect (P<0.05). The addition of gelatin with a concentration of 3% was the best treatment, with a viscosity value of 2847± 89,37 cP (according to SNI 16-4399-1996) and a hedonic value of 5.73<µ<5.91 (preferred by the panelists). While the best treatment for adding liquid smoke as an antioxidant and antibacterial was 0,7% liquid smoke with an antioxidant activity value of 34.87±0.325%, a TPC value of 2.46±0.071 log colonies/g, a pH value of 7.12± 0.025 and did not cause skin irritation.